Characteristics of dry noodles based on sago flour enriched with skipjack tuna (Katsuwonus pelamis): Karakteristik mi kering berbasis tepung sagu yang diperkaya ikan cakalang (Katsuwonus pelamis) - Litaay, Christina; Santoso, Joko; Hariyanto, Bambang; Indriati, Ashri; Andrianto, Moeso; Purwandoko, Pradeka Brilyan; Rahman, Nurhaidar; Indriawati, Indriawati; Sufiandi, Sandi (Jurnal Pengolahan Hasil Perikanan Indonesia, 2024)
Indonesia is one of the countries with the largest consumption of instant noodles. The demand for wheat imports has increased along with the increased consumption of noodles made from wheat flour. Sago flour is recommended for use as a raw material for noodles. The nutritional content of fish can increase the nutritional value of noodle products. This study aimed to determine the optimal concentration of skipjack tuna flour for sago flour-based dry noodles based on their lightness value and consumer preferences. The study included five treatments for sago-based dry noodles: control, skipjack tuna flour 2, 4, 6, and 8%. Dry noodles were then analyzed for lightness value and organoleptic. The best treatment then analyzed chemical composition (protein and ash content) and microstructure. The addition of skipjack tuna flour had a significant effect (p